182k views
1 vote
What is the product of (x-5) and (x-4)? Use the model to find the result

User Yoco
by
5.0k points

1 Answer

4 votes

Answer:

The product of the model is
x^2-9x+25

Explanation:

Given the expression (x-5) and (x-4)

The product of the two factors can be expressed as follows


= (x-5) (x-4)\\=x(x-4)-5(x-5)\\

Opening brackets we have


=x^2-4x-5x+25

Collecting like terms we have


=x^2-9x+25

User Jroith
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.